2019
DOI: 10.22358/jafs/114239/2019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of <i>Nigella sativa</i> and rosemary oils on growth performance, biochemical, antioxidant and immunological parameters, and pathological changes in Japanese quail challenged with <i>Escherichia coli</i>

Abstract: The effects of dietary supplementation with rosemary oil (RO), Nigella sativa oil (NSO) and their combination (NSO+RO) were studied in Japanese quails challenged with Escherichia coli. Thirty hundred quail chicks were randomly allocated to 5 equal groups, each of 3 replicates (20 quails/ replicate). Quails in the negative and positive control groups were fed a basal diet based on maize and soybean with vegetable oil as a lipid source. The experimental dietary groups were fed basal diet with RO, NSO or NSO+RO a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…Genes iap and hlyA are responsible for host cell invasion, while the actA gene is associated with cell-to-cell spread. Our finding agreed with those of previous studies conducted by Tahoun et al, and Şanlibaba et al [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], in which virulence genes were determined in L. monocytogenes isolated from raw milk, animals, and environmental samples. Our findings in virulence gene detection are also supported by the findings of [ 23 ], who reported that virulence genes hlyA , iap, and actA were the most recognized, with prevalence rates of 70.6%, 70.6%, and 52.9%, respectively, and two of the three virulence genes ( hlyA , iap or actA ) were simultaneously detected in six isolates.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Genes iap and hlyA are responsible for host cell invasion, while the actA gene is associated with cell-to-cell spread. Our finding agreed with those of previous studies conducted by Tahoun et al, and Şanlibaba et al [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], in which virulence genes were determined in L. monocytogenes isolated from raw milk, animals, and environmental samples. Our findings in virulence gene detection are also supported by the findings of [ 23 ], who reported that virulence genes hlyA , iap, and actA were the most recognized, with prevalence rates of 70.6%, 70.6%, and 52.9%, respectively, and two of the three virulence genes ( hlyA , iap or actA ) were simultaneously detected in six isolates.…”
Section: Discussionsupporting
confidence: 94%
“…Natural botanical materials and different crude extracts of spices, herbs, and essential oils (EOs) are naturally active elements that have health benefits and protective effects against diseases and foodborne pathogens [ 13 ]. For instance, the EOs of damask rose and orange oil are considered to be promising natural compounds that have antioxidant, antifungal, and antibacterial activity [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…El-Ghammry et al (2002) discovered an opposite finding, in which supplementing with 4 g/kg NSS in the diet showed a little effect on plasma total protein, albumin or globulin. As stated by Aziza et al, (2019), serum total protein and globulin levels were considerably higher in the group supplemented with Nigella sativa oil compared to the positive control group. Meanwhile, the albumin content and albumin/globulin ratio did not indicate any substantial difference among all experimental categories (in quail).…”
Section: Effect Of Nigella Sativa Seeds On Plasma Proteins and Lipid Profilementioning
confidence: 64%
“…Treating with NSS was linked to the increased levels of GSH activity, which may be ascribed to thymoquinone, which possesses potent anti-oxidative and anti-inflammatory properties (Nili-Ahmadabadi et al, 2011). Aziza et al, (2019) discovered that the hepatic GSH level was significantly enhanced just in the groups supplemented with NS oil when compared to both control groups. Accordingly, in a rat model, the fixed and essential oil of NSS had a clear increase in GR and GPx versus the oxidative stress resulted from potassium bromate (Sultan et al, 2015).…”
Section: Effect Of Nigella Sativa Seeds On Antioxidant Indicesmentioning
confidence: 97%
“…It is interesting to note that no high-fat diets (HFD) were administered in the present study before significant anomalies in the HDL and LDL levels were observed (P < 0.05). Recently, Aziza et al (2019) assessed serum biochemical parameters in mice without feeding HFD and observed marked changes between the model (E. coli) and test groups. This again strengthens our position that food pathogens can disrupt many biochemical parameters (including HDL and LDL), and HFD does not need to be administered to observe significant variations in HDL, LDL, TG, and others.…”
Section: Biochemical Analysesmentioning
confidence: 99%